KETIDAKBERPIHAKAN JARGON POLITIK TERHADAP PEREMPUAN DI INDONESIA - Rosida Tiurma Manurung (Jurnal Sosioteknologi, 2009)
It has become a reality that a woman is the second class citizen in the society. The role of the woman had not been counted on. In the field of education, economics, social, religious conviction, also politics, woman has always been gazed at an eye. Furthermore, the woman is the creature who has always been set aside in the world of politics. In the matter of political jargon, the woman did not get the place, did not have the right, and her role was stunted. Development of political jargon today really does not take sides with the woman. Jargon like "a leader must be man", "woman might be apolitical", "woman is only served man", "man is the head, the woman is only a follower", "woman has really became polished in the political campaign", "woman is only as the political colleague", "women is only behind the screen", "women should not dared to entered political field that belongs to the man", "women is only as the implementation and the commodity of activism", "woman became the display window of political views", "women is only as a jack up voice", "woman was made bait in political negotiations", and much other political jargon that very much insulted and stunted the female capacity in the political field. Keyword: jargon politik, ketidakberpihakan terhadap perempuan, dominasi laki-laki